Identifikasi Tingkat Kematangan Buah Tomat Melalui Warna dengan Penerapan Jaringan Saraf Tiruan (JST) - Nazwa Alya Faradita; Lailan Sofinah Harahap (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
The selection of agricultural and plantation products often relies on human perception of fruit color. Manual identification through visual observation has several drawbacks, such as time consumption, fatigue, and varying perceptions of quality. Digital image processing technology enables automatic sorting of products. This study applies the Perceptron learning method to identify tomato ripeness. Tomato images are captured using a webcam, analyzed through color histograms, and identified using artificial neural networks. The identification success rate reaches 43.33%, with outputs categorized as Unripe (10%), Half-Ripe (6.66%), and Ripe (26.66%).